High degree endometrial stromal sarcoma: case report - Molina Loza, Ernesto (2015)
Endometrial stromal sarcoma (ESS) is a rare tumor comprising less than 1% of gynecological malignancies. We report the case of a 24 year old woman with abnormal uterine bleeding who underwent hysterectomy and bilateral oophorectomy for pelvic tumor. At microscopy the neoplasm was composed of malignant proliferation of endometrial stromal cells. Immunohistochemical studies were positive for vimentin and desmin. Clinical and pathologic findings are presented, as well as a review of the new WHO classification and treatment options.